2016
DOI: 10.1016/j.drudis.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the development of therapeutics against coronavirus diseases by targeting N protein

Abstract: The advent of severe acute respiratory syndrome (SARS) in the 21st century and the recent outbreak of Middle-East respiratory syndrome (MERS) highlight the importance of coronaviruses (CoVs) as human pathogens, emphasizing the need for development of novel antiviral strategies to combat acute respiratory infections caused by CoVs. Recent studies suggest that nucleocapsid (N) proteins from coronaviruses and other viruses can be useful antiviral drug targets against viral infections. This review aims to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 103 publications
(129 reference statements)
0
88
0
1
Order By: Relevance
“…The N protein of coronaviruses can be divided into two structural domains (NTD and CTD) and three intrinsically disordered regions (the N-arm, central linker region and C-tail) [10,36]. Previous studies demonstrated the involvement of both the structural domains in binding the RNA of SARS-CoV and MHV (either independently or cooperatively as a bipartite) and showed the involvement of the C-terminal domain in oligomerization of the N protein [19,[30][31][32][33][34][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N protein of coronaviruses can be divided into two structural domains (NTD and CTD) and three intrinsically disordered regions (the N-arm, central linker region and C-tail) [10,36]. Previous studies demonstrated the involvement of both the structural domains in binding the RNA of SARS-CoV and MHV (either independently or cooperatively as a bipartite) and showed the involvement of the C-terminal domain in oligomerization of the N protein [19,[30][31][32][33][34][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The 5′ two-thirds of the viral genome consists of open reading frames (ORF) 1a and 1b that encode the viral nonstructural proteins (nsps), whereas the 3′ one-third consists of ORFs that encode the viral structural proteins, including the spike (S), membrane (M), envelope (E) and nucleocapsid (N), and accessory proteins. The S, M and E proteins form the viral envelope [7][8][9], whereas the N protein is considered the most important protein that interacts with the viral genomic RNA and packages the RNA into virus particles by recognizing a specific sequence, which is termed the packaging signal [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Human coronavirus, discovered in the 1960s, is known to cause severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) (423). Many antiviral candidates (e.g., corticosteroids) potentially inhibit human coronavirus, and more details have been elucidated in recent review articles (445)(446)(447).…”
Section: Viruses Targeted By Neither Vaccines Nor Antiviral Drugsmentioning
confidence: 99%
“…Whether this cross-interaction has beneficial or detrimental effects on viral replication has never been explored. Investigation of the interaction between CoV N proteins could lead to insights into virus evolution, anti-CoV drug development and vaccine design (Chang et al, 2016;Lo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%